The Effectiveness of Problem Based Learning in Term of Student Character on Statistics Lesson - M Farid Nasrulloh; Mas Dhoriful Huda Maghfiroh (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
This study aims to determine the effectiveness of the application of Problem Based Learning in developing students' character in statistical material. The approach used in this research is a quantitative approach with a quasi-experimental type of research. This study used all students of class VII A and VII B of SMP Negeri 2 Sumobito which were divided into two groups, namely class VII A as the experimental group and class VII B as the control group. The instruments used in this study were tests, questionnaires. The test is used to determine the student's ability while the questionnaire is to determine the student's character in Problem Based Learning. The prerequisite test used in this study used a normality test and a homogeneity test with a = 0.05. Hypothesis testing in this study used independent sample t-test on IBM SPSS.21 for windows. The results of the study indicate that the Problem Based Learning model has a positive and significant effect on the development of students' character